Adenosine Triphosphate-Dependent Deoxyribonuclease from Diplococcus pneumoniae: Fate of Transforming Deoxyribonucleic Acid in a Strain Deficient in the Enzymatic Activity - Vovis, Gerald F. (1973)
The adenosine triphosphate-dependent deoxyribonuclease is required for wild-type levels of deoxyribonucleic acid (DNA) repair and genetic recombination. In an attempt to determine the physiological function of this enzyme in pneumococcal transformation, the fate of transforming DNA was followed in a wild-type strain and in a strain lacking the enzymatic activity. The qualitative and quantitative findings were closely comparable in the two strains through the step of physical association of a single strand of donor DNA with the recipient chromosome. These results are interpreted to mean that the enzyme may be involved in the subsequent hypothetical removal of excess polynucleotide sequences during conversion of the presumed hydrogen-bonded intermediate into a covalently linked recombinant structure.